2019
DOI: 10.1105/tpc.18.00431
|View full text |Cite
|
Sign up to set email alerts
|

The Systems Architecture of Molecular Memory in Poplar after Abiotic Stress

Abstract: Throughout the temperate zones, plants face combined drought and heat spells in increasing frequency and intensity. Here, we compared periodic (intermittent, i.e., high-frequency) versus chronic (continuous, i.e., high-intensity) drought-heat stress scenarios in gray poplar (Populus3 canescens) plants for phenotypic and transcriptomic effects during stress and after recovery. Photosynthetic productivity after stress recovery exceeded the performance of poplar trees without stress experience. We analyzed the mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 87 publications
1
26
0
Order By: Relevance
“…Among these 18 genes, two Myb-containing domain genes Myb108 (Prupe.1G111700) and Myb102 (Prupe.4G192000) and one homeobox 7 (HB7, Prupe.3G316600) were differentially expressed in both species. Past studies reported that HB7 is a stress response protein positively regulated by the ABA pathway (Söderman et al, 1996;Georgii et al, 2019). The high expression level of HB7 transcripts during ecodormancy in apricot and peach suggests high concentrations of ABA, which may be acting to repress bud break during ecodormancy.…”
Section: Plant Hormones Are Involved In the Endodormancy To Ecodormanmentioning
confidence: 96%
“…Among these 18 genes, two Myb-containing domain genes Myb108 (Prupe.1G111700) and Myb102 (Prupe.4G192000) and one homeobox 7 (HB7, Prupe.3G316600) were differentially expressed in both species. Past studies reported that HB7 is a stress response protein positively regulated by the ABA pathway (Söderman et al, 1996;Georgii et al, 2019). The high expression level of HB7 transcripts during ecodormancy in apricot and peach suggests high concentrations of ABA, which may be acting to repress bud break during ecodormancy.…”
Section: Plant Hormones Are Involved In the Endodormancy To Ecodormanmentioning
confidence: 96%
“…Using periodically combined drought and heat treatments, several stress-related memory genes were identified through tissue-specific transcriptomic profiling studies in poplar. Among them, the homologs of Arabidopsis HOMEOBOX7 ( HB7 ) were proposed as the most prominent candidates enhancing plant photosynthesis during stress recovery ( Georgii et al, 2019 ). In conclusion, epigenetic regulation and stress memory play important roles in drought response and tolerance, but their regulatory roles have not been well defined and deserve further investigations.…”
Section: Epigenetic Regulation Of Drought Responsementioning
confidence: 99%
“…A survey for related studies in the literature (E[CO 2 ] and water stress) was performed in order to compare the sorghum GPR expression pattern to Populus trichocarpa (Georgii et al, 2019), Glycine max (Bencke-Malato et al, 2019), Oryza sativa (Shen et al, 2011), and Zea mays (Opitz et al, 2014). After the selection of the studies, we performed the best hits identification between S. bicolor and each other species via Blastp analysis based on the following thresholds: percentage of identity ≥ 70% and e-value < 1e-10.…”
Section: Methodsmentioning
confidence: 99%